Three-Dimensional Visualization of Mouse Endometrial Remodeling After Superovulation - Qu, Yongcun; Zhang, Jia; Guo, Shanshan; Zhang, Liwen; Qian, Jingjing; Zhu, Xili; Duan, Enkui; Zhang, Ying (Frontiers in Cell and Developmental Biology, 2022)
Uterine status determines pregnancy success. Although it is well known that superovulation operations can disrupt uterine function, our understanding of the morphological changes in the uterine endometrium at the three-dimensional (3D) level is limited. Here, combining tissue clearing with 3D deep imaging, we reveal an increase in epithelial density and angiogenesis after ovarian stimulation, which is accompanied by a circulating surge in P4 levels. Using an ovariectomized mouse model, we further detected the separate regulatory effects of P4 and E2 on uterine endometrium, with P4 promoting endothelial cell growth and E2 inducing epithelial proliferation; additionally, we observed that the effects of E2 can be partially neutralized by P4, and vice versa. By analyzing 3D uterine imaging, we discovered an interesting phenomenon in which the growing blood vessels closely surround the remodeling uterine epithelium, indicating a close relationship between angiogenesis and epithelial growth. These findings provide new insight into uterine epithelial changes and angiogenesis at the 3D level and explain a potential reason for endometrial changes due to the low implantation rate in patients undergoing clinical superovulation.